Bed-level adjustements in the Po River catchment (Northern Italy) - Rinaldi, Massimo (Italian journal of engineering geology and environment, 2021)
<span data-sheets-value="{"1":2,"2":"An analysis of bed elevation changes by comparing two or more sets of bed profiles was carried out along the Po River and 11 other streams of its catchment, totalling 21 segments, over a period covering approximately the past 70 years. A comparison of two sets of aerial photos, taken during the same period, was also carried out with a view to discussing relations between bed-level and planform adjustments. The results showed that bed incision was ubiquitous in all rivers, occurring in 20 out of 21 segments, with segment-averaged values of 0.27 to 5.49 m and at-a-site values of 2.37 to 12.08 m. A first period of major bed lowering (during the first few decades after 1950) was followed by a trend reversal in 7 out of 21 cases, whereas aggradation was followed by further incision in 5 cases. The results of changes in channel width and planform pattern showed that narrowing occurred in all cases and that changes in channel morphology occurred in 31% of the total analysed river length, the most frequent case being a change from transitional to single-thread. Changes from an initial multi-thread to a transitional or single-thread morphology were associated with a higher degree of narrowing, whereas changes from a transitional to a single-thread morphology were associated with the highest degree of bed lowering. A summary evolutionary model was derived, representing an application of the original Surian and Rinaldi model to the alluvial rivers of the Po River catchment."}" data-sheets-userformat="{"2":15297,"3":{"1":0},"9":0,"10":1,"11":3,"12":0,"14":{"1":2,"2":0},"15":"Arial","16":8}">An analysis of bed elevation changes by comparing two or more sets of bed profiles was carried out along the Po River and 11 other streams of its catchment, totalling 21 segments, over a period covering approximately the past 70 years. A comparison of two sets of aerial photos, taken during the same period, was also carried out with a view to discussing relations between bed-level and planform adjustments. The results showed that bed incision was ubiquitous in all rivers, occurring in 20 out of 21 segments, with segment-averaged values of 0.27 to 5.49 m and at-a-site values of 2.37 to 12.08 m. A first period of major bed lowering (during the first few decades after 1950) was followed by a trend reversal in 7 out of 21 cases, whereas aggradation was followed by further incision in 5 cases. The results of changes in channel width and planform pattern showed that narrowing occurred in all cases and that changes in channel morphology occurred in 31% of the total analysed river length, the most frequent case being a change from transitional to single-thread. Changes from an initial multi-thread to a transitional or single-thread morphology were associated with a higher degree of narrowing, whereas changes from a transitional to a single-thread morphology were associated with the highest degree of bed lowering. A summary evolutionary model was derived, representing an application of the original Surian and Rinaldi model to the alluvial rivers of the Po River catchment.